2020
DOI: 10.48550/arxiv.2010.08083
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Near-Linear Time Homomorphism Counting in Bounded Degeneracy Graphs: The Barrier of Long Induced Cycles

Abstract: Counting homomorphisms of a constant sized pattern graph H in an input graph G is a fundamental computational problem. There is a rich history of studying the complexity of this problem, under various constraints on the input G and the pattern H. Given the significance of this problem and the large sizes of modern inputs, we investigate when near-linear time algorithms are possible. We focus on the case when the input graph has bounded degeneracy, a commonly studied and practically relevant class for homomorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Specifically, they showed that H-homomorphisms in bounded-degeneracy graphs can be counted in time Õ(n) if and only if H contains no induced cycles of length 6 or larger 6 . A similar result has been independently obtained in [7]. These results highlight the important role played by cycles of length at least 6, as being the minimal graphs whose homomorphisms cannot be counted in (almost) linear time (in bounded-degeneracy graphs).…”
Section: Counting Homomorphisms In Degenerate Graphssupporting
confidence: 84%
See 2 more Smart Citations
“…Specifically, they showed that H-homomorphisms in bounded-degeneracy graphs can be counted in time Õ(n) if and only if H contains no induced cycles of length 6 or larger 6 . A similar result has been independently obtained in [7]. These results highlight the important role played by cycles of length at least 6, as being the minimal graphs whose homomorphisms cannot be counted in (almost) linear time (in bounded-degeneracy graphs).…”
Section: Counting Homomorphisms In Degenerate Graphssupporting
confidence: 84%
“…To establish that this is indeed the "hardest orientation", we show (roughly speaking) that for every DAG H and for every directed subdivision H ′ of H, counting H ′homomorphisms can be reduced to counting H-homomorphisms (in input DAGs of bounded maximum degree). It is easy to see that every acyclic orientation H of C ℓ (with at least two sources) is a directed subdivision of the alternating orientation of C ℓ ′ for some even ℓ ′ ≤ ℓ, and that ℓ ′ = ℓ if and only if H itself is alternating 7 . It follows that the running time of counting C ℓ -homomorphisms is dominated by the running time of counting homomorphisms of alternating orientations of cycles of even length at most ℓ.…”
Section: Our Resultsmentioning
confidence: 99%
See 1 more Smart Citation